Psoriatic arthritis. - Bessa, I; Santos, H; Soles, I; Monteiro, T; Pinto, B (Acta Médica Portuguesa, 2001)
The Psoriasis Arthritis witch was considered for many years as a late complication of the Psoriasis, is presently known as a chronical systemic disease, resulting w from the coexistence of a chronical evolutive poliarthropaty and a skin disease, the Psoriasis. The authors make a brief revision of the etiopathogeny, clinics and treatment of the Psoriasis arthritis and show a retrospective analysis of the clinical cases of 19 patients with Psoriatic Arthritis followed at the Medicine Consultation Reumathologie.